Free Vibrational Behavior of Bi-Directional Functionally Graded Composite Panel with and Without Porosities Using 3D Finite Element Approximations - S. Ghatage, Pankaj; Sudhagar, P. Edwin (International Journal of Integrated Engineering, 2023)
Abstract: In the present study, the frequency characteristics of bi-directional functionally graded panels in rectangular planform with and without porosities are examined using 3D finite element approximations. In this work, the graded panel is consisted of metal and ceramic material, in which material properties vary smoothly in two directions. The material properties of this highly heterogeneous material are obtained using the Voigt model via extended power-law distribution of volume fractions. The present model is developed using a customized computer code and discretized using three dimensional solid 20-noded quadrilateral elements. The mesh refinement is carried out to conduct the convergence test and the validation test by comparing the obtained results with the previous reported results. At a later stage, a comprehensive parametric study is conducted through numerical illustrations which reveal that the geometrical and material parameters of bi-directional functionally graded panel affect its frequency characteristics, significantly.